2009
DOI: 10.1007/s10750-009-9926-2
|View full text |Cite
|
Sign up to set email alerts
|

Can hydrologic management practices of rice fields contribute to macroinvertebrate conservation in southern Brazil wetlands?

Abstract: The expansion of rice fields is one of the main human activities responsible for the decline of natural wetlands throughout the world. However, rice fields have been recognized as having considerable potential value for many aquatic species. In this sense, an important question from the point of view of biodiversity conservation is the adequacy of these agricultural wetlands as an integrated managed landscape that contributes to maintain a rich biodiversity. The two main questions of this study were: (1) Do ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…In this phase, the agricultural land is drained and surface water is not present. Since these irrigated rice fields show a high invertebrate diversity (Stenert et al 2009), and the invertebrate resting stages can remain viable over many years in the wetland sediments (Wiggins et al 1980;Boulton and Lloyd 1992;Brock et al 2003;Jenkins and Boulton 2007), the present study tested the hypothesis that the hydrologic regime adopted in rice fields of southern Brazil does not compromise the viability of resting stages of aquatic invertebrates. Furthermore, our study analyzed how richness, density, and composition of drought-resistant aquatic invertebrates respond to experimental rehydration after different periods without surface water in rice fields of southern Brazil.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this phase, the agricultural land is drained and surface water is not present. Since these irrigated rice fields show a high invertebrate diversity (Stenert et al 2009), and the invertebrate resting stages can remain viable over many years in the wetland sediments (Wiggins et al 1980;Boulton and Lloyd 1992;Brock et al 2003;Jenkins and Boulton 2007), the present study tested the hypothesis that the hydrologic regime adopted in rice fields of southern Brazil does not compromise the viability of resting stages of aquatic invertebrates. Furthermore, our study analyzed how richness, density, and composition of drought-resistant aquatic invertebrates respond to experimental rehydration after different periods without surface water in rice fields of southern Brazil.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, irrigated rice fields have been regarded as a refuge for biologic diversity throughout the world (Fernando et al 1979;Bambaradeniya and Amerasinghe 2003;Elphick and Oring 2003), including southern Brazil (Stenert et al 2009;Rolon and Maltchik 2010). However, the potential for recovery of biologic communities via dormant propagule banks has not been investigated in rice field sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Rice fields are also used to graze various livestock, ranging from cattle (e.g. in South America; Stenert et al 2009) to ducks (e.g. in China; Muzaffar et al 2010).…”
mentioning
confidence: 99%
“…Worldwide, several studies have demonstrated its importance in biological conservation, since can improve habitats for many species of aquatic invertebrates, as insects, molluscs, crustaceans; and vertebrates, as fish, amphibians, reptiles and birds (Bambaradeniya, 2000;Czech & Parsons, 2002;Bambaradeniya & Amerasinghe, 2003;Manley, 2008; Elphick, Parsins, Fasola, & Mugica, 2010). In the Neotropical region, different studies have been carried out about the biodiversity of macroinvertebrates, amphibians, birds and macrophytes in the irrigated channels of rice fields (Blanco, López-Lanús, Dias, Azpiroz, & Rilla, 2006;Stenert, Bacca, Maltchik, & Rocha, 2009;Machado & Maltchik, 2010;Maltchik, Rolon, Stenert, Machado, & Rocha, 2011). Specifically in Northeastern Argentina, the macroinvertebrates, planorbids, amphibians, fish and birds diversity has been the subject of studies in rice fields Duré, Kehr, Schaefer, & Marangoni, 2008;Blanco & de la Balze, 2011).…”
Section: Introductionmentioning
confidence: 99%